2017
DOI: 10.3390/environments4040076
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Dustiness, Specific Allergens, and Endotoxin in Bulk Soya Imports

Abstract: Soya is an important bulk agricultural product often transported by sea as chipped beans and/or the bean husks after pelletisation. There are proven allergens in both forms. Bulk handling of soya imports can generate air pollution containing dust, allergens, and pyrogens, posing health risks to dockside workers and surrounding populations. Using an International Organization for Standardization (ISO) standardised rotating drum dustiness test in seven imported soya bulks, we compared the generated levels of dus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Our two dock studies [19] [paper in preparation] identified that gravimetric measurements only explained 50-70% of the variation in the airborne levels of the two allergens measured, even in a relatively constrained number of bulks. The lack of a good relationship found between gravimetric dust and allergen (HSP and STI) levels in the respiratory-sized fraction generated by drum dustiness tests confirms this [18]. HSE's second dock study suggested that gravimetric dust measurements only explained about 29-57% of the variation in endotoxin levels over the 2 days of sampling.…”
Section: Controlling Exposure To Soya Dustmentioning
confidence: 88%
See 4 more Smart Citations
“…Our two dock studies [19] [paper in preparation] identified that gravimetric measurements only explained 50-70% of the variation in the airborne levels of the two allergens measured, even in a relatively constrained number of bulks. The lack of a good relationship found between gravimetric dust and allergen (HSP and STI) levels in the respiratory-sized fraction generated by drum dustiness tests confirms this [18]. HSE's second dock study suggested that gravimetric dust measurements only explained about 29-57% of the variation in endotoxin levels over the 2 days of sampling.…”
Section: Controlling Exposure To Soya Dustmentioning
confidence: 88%
“…has set a suggested health-based exposure limit for airborne endotoxin [17]. Endotoxin has been found to be extractable from soya meal and husk and becomes airborne when handling bulk [18][19][20][21].…”
Section: Soybean For Human Consumption and Animal Feedmentioning
confidence: 99%
See 3 more Smart Citations